Fecal Shedding of 2 Novel Live Attenuated Oral Poliovirus Type 2 Vaccine Candidates by Healthy Infants Administered Bivalent Oral Poliovirus Vaccine/Inactivated Poliovirus Vaccine: 2 Randomized Clinical Trials . (5th October 2021) - Gast, Christopher; Bandyopadhyay, Ananda S; Sáez-Llorens, Xavier; De Leon, Tirza; DeAntonio, Rodrigo; Jimeno, José; Aguirre, Gabriela; McDuffie, Larin M; Coffee, Elizabeth; Mathis, Demetrius L; Oberste, M Steven; Weldon, William C; et al.
Abstract: Background: Primary intestinal immunity through viral replication of live oral vaccine is key to interrupt poliovirus transmission. We assessed viral fecal shedding from infants administered Sabin monovalent poliovirus type 2 vaccine (mOPV2) or low and high doses of 2 novel OPV2 (nOPV2) vaccine candidates. Methods: In 2 randomized clinical trials in Panama, a control mOPV2 study (October 2015 to April 2016) and nOPV2 study (September 2018 to October 2019), 18-week-old infants vaccinated with bivalent oral poliovirus vaccine/inactivated poliovirus vaccine received 1 or 2 study vaccinations 28 days apart. Stools were assessed for poliovirus RNA by polymerase chain reaction (PCR) and live virus by culture for 28 days postvaccination. Results: Shedding data were available from 621 initially reverse-transcription PCR–negative infants (91 mOPV2, 265 nOPV2-c1, 265 nOPV2-c2 recipients). Seven days after dose 1, 64.3% of mOPV2 recipients and 31.3%–48.5% of nOPV2 recipients across groups shed infectious type 2 virus. Respective rates 7 days after dose 2 decreased to 33.3% and 12.9%–22.7%, showing induction of intestinal immunity. Shedding of both nOPV2 candidates ceased at similar or faster rates than mOPV2. Conclusions: Viral shedding of either nOPV candidate was similar or decreased relative to mOPV2, and all vaccines showed indications that the vaccine virus was replicating sufficiently to induce primary intestinal mucosal immunity. Abstract : Fecal shedding of 2 novel oral poliovirus type 2 vaccine (OPV2) candidates and Sabin mOPV2 was assessed in bOPV/inactivated polio vaccine–immunized infants. Shedding of both candidates was similar or lower in quantity and duration compared with mOPV2. All 3 vaccines induced intestinal immunity.